Innovative Pasta with High Nutritional and Health Potential - Gazza, Laura; Nocente, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dry pasta is one of the most popular staple foods worldwide due to its convenience in terms of affordability, versatility, long shelf life, as well as sensory and nutritional value. As such, it represents a suitable carrier for health-promoting substances providing specific physiological functions. This Special Issue deals with the continuum aspects, "from seed to fork", that could have an impact on the nutritional, sensory, and technological aspects of pasta. In this Special Issue, we aimed to publish innovative research and review papers on physico-chemical and sensorial characteristics, nutritional value, functional and technological properties of pasta, and pasta-making processes. New raw materials, new functional ingredients, up-cycling of waste materials, in vivo experiments to test the effect of assumption of the supplemented pasta, and innovative packaging systems will also be addressed in this Special Issue. Predictions of pasta quality adopting chemometrics as well as multi-variate and statistical data analysis approaches were welcomed. Finally, in the medium term, the international pasta market is expected to stay negative unless tangible product innovations are introduced, particularly regarding the technological innovations aimed at improving the products' health benefits. This Special Issue aimed to provide a fundamental understanding and present the current strategies to improve the technological, nutritional, and sensory properties of pasta.